Free-space optical data link using Peltier-cooled quantum cascade laser - Blaser, Stéphane; Hofstetter, Daniel; Beck, Mattias; Faist, Jérôme (My University, 2001)
The authors demonstrate a free-space optical data link over 350 m using a Peltier-cooled 9.3 µm quantum cascade laser operating at a duty cycle of almost 50%. On the emitter side, a Ge lens was used for beam collimation and a flat mirror for beam steering, while on the receiver side, a fast room-temperature HgCdTe detector in combination with a Φ = 16 cm mirror telescope detected the incoming signal. Short pulses at a maximum repetition rate of 330 MHz were successfully transmitted. The signal-to-noise ratio of the measurement was limited by the power equivalent noise of the detector.